Learning disabilities and e-information : navigating the electronic hypermaze - Williams, Peter (Emerald Publishing Limited, 2020)
Digital Technology is becoming ever more used by people with learning disabilities for information, entertainment and to enjoy self-expression. Despite this, there is a paucity of research into how this cohort negotiate electronic interfaces, interpret images, navigate pages and read online; what barriers there might be, and how these could be obviated. This book explores these issues, establishing how these and other factors facilitate or inhibit information access and behaviour more generally. There are plenty of guidelines and accessibility standards regarding electronic information presentation, but most are outdated or have been formulated without empirical evidence. Unlike prior literature this book is the result of many years's research in the field, considers specific information contexts, and develops new concepts in information behaviour. It is written in non-technical, jargon-free language, relevant for academics, students and professionals; from human-computer interaction researchers, learning disability specialists and information scientists to formal and informal carers and supporters, college tutors, family members and others.
Keywords: Learning disabilities.; Cyberinfrastructure.; Education -- Special Education -- Developmental & Intellectual Disabilities.; Teaching of students with specific learning difficulties, needs.; elektronické knihy; electronic books